Livestock and climate solutions hub: Delivering an equitable transition to sustainable and low emission livestock systems in low- and middle-income countries - International Livestock Research Institute (International Livestock Research Institute, 2024)
A multi-stakeholder approach to transitioning LMIC’s livestock systems to low, healthy, resilient, and profitable food systems by 2040